Intra-Africa regional trade comovements and shock transmission: A baseline for AfCFTA - Lord Kwaku Mensah (Cogent Economics & Finance, 2023)
This paper examines the trade co-movements and shock spillover across four African geographic regions. Specifically, we were motivated by the very low intra-trade activities in Africa, despite increased regionalism to study the possibility of a country's trade shock being transferred to its trading partners on the continent. Knowing the trade connectedness and shock transmission among African countries will serve as a baseline for the AfCFTA implementation. In our analysis, we considered the four African regional quarterly data between 2005 and 2021 from UNCTAD. The continent was divided into four regions namely, Western, Middle, Eastern, and Southern Africa. We divided the time into pre- and post-AfCFTA periods. The Dynamic Conditional Correlation (DCC) and the Diebold and Yilmaz (2012) models were adopted to determine the trade co-movement and the shock spillover respectively. The results show different trade co-movement and trade shock spillovers among the regions at different times. The trade co-movement seems to be dominant between the Middle and Southern African regions. Further analysis shows the presence of trade shock transmission across all four regions. The Western African region exhibits a sign of the biggest trade shock receiver from the other regions, while the Southern African regions turn out to be the largest contributor of trade shocks to the other regions both in the post and pre- AfCFTA period. The study contributes by sending a signal to AfCFTA implementers that trading on the African continents behaves differently among the various geographic regions. It also provides early warning signal for AfCFTA policy implementation.
Keywords: 330; AfCFTA; African Intra-trade; co-movement; trade shock spillovers